DESIGN OF KEMPLANG CRACKERS DRYER USING TRAY DRYER BY UTILIZING BIOMASS ENERGY - Sari, Della Yusfita; Zamhari, Mustain; Junaidi, Robert (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
The drying process on kemplang crackers is one of the factors that determine the quality of the resulting product. Conventional drying has many disadvantages, namely fluctuating heat and poor hygiene that will affect product quality. So that kemplang crackers can be stored for a long time, it is necessary to reduce the water content of kemplang crackers. Drying kemplang crackers can use a drying rack with a biomass energy source from coconut shells. This study aims to design a tray dryer with biomass energy to obtain dryer performance based on the drying rate and to obtain a product that meets SNI No. 8272-2016. The treatments that were varied were set point temperatures of 55oC, 60oC, 65oC, and 70oC with mass variations of 50 gr, 100 gr, and 150 gr. The results showed that the optimum drying conditions at 70oC for 4 hours with an air velocity of 5.2 m/s2 obtained 9,84% moisture content in 50 gr kemplang crackers, 15.39% in 100 gr crackers and 19,2 in kemplang crackers 150 gr and a drying rate of 0,035028 kg/hour m2. The drying process requires 5,24 kg of dried coconut shell to produce heat energy of 95.358,81024 KJ with a by-product in the form of liquid smoke.